Kekuatan Awal Stabilisasi Gambut Menggunakan Geopolimer Dengan Variasi Modulus Silikat - Ananda, Yazid Fahmi; Wibisono, Gunawan; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2022)
Peat is a source of quite a lot of organic matter. The fibrous texture of peat soil makes the soil has low shear strength. To overcome the low bearing capacity of the peat, it is necessary to stabilize the peat soil. Soil stabilization with a mixture of fly ash geopolymer which is rich in silica and alumina is a new innovative material that is more environmentally friendly and can be developed as an alternative to cement. The purpose of this study is to increase the bearing capacity of peat soil and minimize the use of cement in mixture below 250kg/m3 through UCS (Unconfined Compressive Strength) test. The variations of the silicate modulus used in this research were ms 1, ms 1.5, and ms 2 with a concentration of 10M NaOH and a curing time of 7 and 14 days.. The results of the study shows that the hybrid geopolymer mixture could increase the bearing capacity and shear strength of peat with the optimum compressive strength value of 23.96 kPa at 7 days of curing time and the lowest compressive strength of 17.30 kPa at 14 days of curing time.Keywords: peat soil, geopolymer, soil stablization, cement